The Sustainable Development Goals and the Impact of the Covid-19 Pandemic in Nigeria - Thelma Mohammed, Ngozi; Akinniyi, Praise (Kashere Journal of Humanities, Management and Social Sciences, 2022)
Worsened by increasing violent conflicts and plummeting oil prices, the Covid-19 pandemic has further turned Nigeria off the path of achieving the 2030 Sustainable Development Goals (SDGs). The strict lockdown measures greatly affected economic activities, especially, farming, and has resulted in food shortages, loss of businesses and increased poverty. The ongoing security crisis in the country poses continued threats to sustainable development as well as prompt state response to containing the virus pandemic in the conflict affected areas. The pandemic has greatly affected humanitarian access and operations in those areas and thus beg for urgent interventions. This study employed the concept of Sustainable Development as a theoretical tool to critically analyze the impact of the Coronavirus crises amidst the quagmire of challenges already contending with the attainment of the SDGs in Nigeria. The paper, which draws from secondary sources of data and personal observations, finds out among other things, the vulnerability of the northeastern region to the virus pandemic, the worsening living conditions of the people and urgent need for developmental interventions across the country. Government, therefore, needs to refocus on the SDGs not just as a Covid-19 recovery plan, but more importantly for sustainable development in the country.